Electromechanical characterization of piezoelectric polymer thin films in a broad frequency range - González, Martín Germán (2014)
Piezoelectric materials are usually characterized using resonant methods. However, piezoelectric polymers are used in broadband devices, thus requiring characterization over a wide range of frequencies. In this work, we present a non-resonant method for the broadband electromechanical characterization of piezoelectric polymer thin films. The procedure is based on measuring the complex capacitance of a sample of known geometry under three conditions: free, blocked and immersed in a fluid of known acoustic properties. The behaviour of the sample under study is modelled as a one-dimensional transducer and treated as a two-port network that relates the measurable electrical and mechanical variables. Also, the sample is considered as a free-space radiator when immersed in a fluid. The method determines the intensive and the equivalent circuit parameters of piezoelectric polymer films, allowing the characterization of elastic and electrical properties in a broad frequency range. In order to test the method, we performed isothermal capacitance measurements on a sample of poly(vinylidene fluoride) at a temperature of 298 K. The sample was measured along the direction of the poling field and in the frequency range from 10 Hz to 10 MHz. The results given by the method agree with those reported by other authors.